Construction of uniform ZrO2 nanoshells by buffer solutions. Issue 37 (24th August 2018) - Tao, Xian-Sen; Sun, Yong-Gang; Lin, Xi-Jie; Hu, Lin-Lin; Sun, Tian-Qi; Zhang, Dong; Cao, An-Min; Wan, Li-Jun
Abstract : The growth kinetics of ZrO2 could be well-tuned in buffer solutions, which led to uniform ZrO2 nanoshells. Abstract : We identified that the growth kinetics of ZrO2 could be well-tuned in a CH3 COOH–CH3 COONa based buffer solution, which provided an efficient way to build uniform ZrO2 nanoshells on various substrates. Using this synthetic strategy, yolk–shell structured Pd@ZrO2 is demonstrated as a promising catalyst for methane oxidation.